On creativity, liberty, love, and the beauty of the law - Breyfogle, Todd (Reading Augustine, 2018)
The Reading Augustine series presents concise, personal readings of St. Augustine of Hippo from leading philosophers and religious scholars. Todd Breyfogle's On Creativity, Liberty, Love and the Beauty of the Law introduces readers to Augustine's understanding of law as an arena in which the possibilities of creative freedom are reconciled with the needs of natural and civil order. It places Augustine's conception of law in the broader mosaic of his ideas about how human beings are bound together individually, socially, and spiritually. Seasoned readers of Augustine will see this fundamental element of his thought in a different light, even as those less familiar with Augustine are introduced to the thrill of following how he makes sense of the complexities of nature, history, and the human spirit